Visual flow-based programming plugin for brain–computer Interface in computer-aided design - Xu, Tong Bill; Kalantari, Saleh (Automation in construction, 2024)
Over the last half century, the main application of Brain–Computer Interfaces (BCIs) has been controlling wheelchairs and neuroprostheses, or generating text or commands for people with restricted mobility. There has been very limited attention in the field to applications for computer-aided design (CAD), especially in the built environment, despite the potential of BCIs to provide a new form of environmental interaction. This paper introduces Neuron, a BCI tool that enables designers with little experience in neuroscience or computer programming to: (1) gain access to neurological data, along with established metrics relevant to design; (2) create BCI interaction prototypes, both with digital on-screen objects and physical devices; and (3) evaluate designs based on neurological information and record measurements for further analysis. After detailing the BCI tool's development, the article showcases its capabilities through two case studies within the architectural design and built environment, followed by an evaluation of the tool's performance and a discussion of its implications, limitations, and areas for future improvement. •A BCI software tool was developed for EEG data acquisition, signal processing, feature extraction, and visualization.•NEURON enables brain-controlled generative design process•NEURON enables BCI prototyping for intelligence control system with visual programming•NEURON provides an accessible platform for integrating BCI into design, promoting interdisciplinary research and practical applications